10 years studies of business management knowledge sharing in social media: a bibliometric analysis and future research agenda / Aini Qamariah Yusof … [et al.] - Yusof, Aini Qamariah; Eshak, Erratul Shela; Zakirai@Zakaria, Norlida; Idrus, Syukurriah; Wan Hashim, Wan Nor Syazana (2023)
This paper runs a bibliometric analysis to present the characteristics and evolution of the research publications on knowledge sharing. Our sample is composed of all the documents from the SCOPUS for the period of 2013-2023. The findings show that knowledge-sharing research activity has been varying for the past 10 years. The analysis also reveals the numbers of publications per year, including the the most relevant sources, the most global cited documents. The results on most used keywords are essential point for future researcher, and all recent concept and trend topic on this area are also important to see what future agenda are moving toward knowledge-sharing in social media. In addition, it would be interesting to assess the continuous proliferation of new social media used for knowledge-sharing applications. The bibliometric studies therefore add substantially to the understanding of scientific production assessment that has significant implications for universities and policymakers. to evaluate the development and trends in business management knowledge sharing. By analyzing the scientific literature, this study can gain insights into the state of the art and identify gaps or areas for further investigation. It also examines citation patterns and co-citation networks, identifying influential works and researchers in a particular field. Bibliometric analysis is a computerized quantitative statistical analysis applied to publications, which can be performed using tools such as open-source R-package bibliometric. The period under scrutiny is 2013-2023. This study employs bibliometric analysis to unravel the intricate trends and dynamics of business management knowledge sharing through social media platforms over a span of one decade with 1478 papers related to business management knowledge sharing using social media from 2013 to 2023. limitations include data quality, discipline variation, and challenges in research evaluation. Researchers should be aware of these limitations and use bibliometrics in conjunction with other research methods to gain a comprehensive understanding of the research landscape. One limitation is that it relies on the availability and accuracy of bibliographic data from databases such as Scopus, the results of bibliometric analysis may be influenced by the coverage and quality of the data sources used. provide a comprehensive overview of business management and knowledge sharing in social media, as well as looking at the evolution of business management knowledge sharing for 10 years.